Leather glass composition, leather glass as well as preparation method and application of leather glass

By controlling the composition and process of leather glass, the problem of difficult to meet the wide spectrum response, radiation resistance and low refractive index in the prior art is solved, and the efficient application of leather glass in the aerospace field is achieved, and the imaging clarity and service life are improved.

CN119750916AActive Publication Date: 2025-04-04CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411946356.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to meet the requirements of leather glass in terms of wide spectrum response, radiation resistance and low refractive index, resulting in the inability to meet the needs of long-distance detection in the aerospace field.

Method used

By controlling the composition and content of the leather glass, including quartz sand, boric acid, alumina, sodium carbonate, potassium hydrofluoride, calcium fluoride, alkaline magnesium carbonate, lithium carbonate, zinc oxide and cerium oxide, a non-metallic container and a smelting furnace of refractory materials, oxygen is introduced into the glass liquid to control the valence state of the variable valence elements.

Benefits of technology

The spectral transmittance of the leather glass with a wavelength range of 330 to 2000 nm is achieved at a thickness of 100 mm, and the transmittance attenuation rate of ≤3% for 500 hours of irradiation at 6.4kGy irradiation dose is ≤3%, and the refractive index is ≤1.50. It has good crystallization resistance, moisture resistance and chemical stability, meeting the preparation process requirements of optical fiber image transmission arrays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213748170000021
    Figure BDA0005213748170000021
  • Figure BDA0005213748170000121
    Figure BDA0005213748170000121
  • Figure BDA0005213748170000131
    Figure BDA0005213748170000131
Patent Text Reader

Abstract

The invention provides a leather glass composition, leather glass as well as a preparation method and application of the leather glass. The composition comprises the following components in percentage by mass: 60-75% of quartz sand, 1.5-15% of boric acid, 1-5% of aluminum oxide, 1-10% of sodium carbonate, 1-8% of potassium bifluoride, 1-8% of calcium fluoride, 0-5% of basic magnesium carbonate, 0-8% of lithium carbonate, 0-5% of zinc oxide and 0-2% of cerium oxide. In the raw materials, the total content of the impurities Fe, Cu and Mn is smaller than or equal to 3 ppm, and the total content of the impurities Nd, Pr, U, Er, Eu, Tb and Dy is smaller than or equal to 2 ppm. The technical problem to be solved is how to prepare the leather glass, so that the leather glass can simultaneously meet the requirements of wide spectral response, radiation resistance and low refractive index, and the spectral transmittance is greater than or equal to 75% in the wavelength range of 330-2000nm under the thickness of 100mm. When the glass is applied to high-ray irradiation and wide-spectrum detection environments in the aerospace field, the imaging definition of the glass can be effectively improved, the service life of the glass can be effectively prolonged, and long-distance detection is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass manufacturing, and in particular to a leather glass composition, leather glass, and a preparation method and application thereof. Background Art

[0002] The fiber optic image transmission array is composed of tens of millions of micron-level optical fibers tightly and regularly arranged and fused together. It can transmit images with high fidelity and has the characteristics of zero optical thickness, large numerical aperture, and high resolution. It includes optical fiber panels, fiber optic image inverters, fiber optic light cones, fiber optic image transmission bundles, etc. It can be used in aerospace, low-light level night vision, medical diagnosis and other fields. It is a high-tech cutting-edge product in the optoelectronics industry.

[0003] The optical fiber image transmission array uses a core glass with a high refractive index and a skin glass tube with a low refractive index, and arranges the plates by combining rods and tubes with drawn single wires; the absorber glass is drawn into wires and inserted into the arranged single wires, and the absorber glass mainly absorbs stray light; it is then bundled into a composite rod and subjected to wire drawing, plate arrangement, hot melt pressing to form a blank plate section, and then precision deep processing. It is mainly used to achieve high-definition image transmission, which solves the problem of low resolution and poor clarity of the system's field image, and improves the imaging clarity.

[0004] At present, fiber optic image arrays are used for long-distance detection in radiation-irradiated environments such as space. The glass must have a wide spectrum and high transmittance to obtain a longer detection distance, and the glass must be able to withstand radiation. It is difficult to meet both requirements at the same time. Skin glass is the core component of the fiber optic image array. Its main function is to form a total reflection layer at the interface between the core and the skin. For skin glass, due to its smaller scale inside the optical fiber panel, it is more prone to defects during the manufacturing process. It must be better than core glass in terms of radiation resistance and ultraviolet transmission performance. However, there is no skin glass in the existing technology that can simultaneously meet the three conditions of wide spectrum response, radiation resistance and low refractive index, which makes it impossible to meet the requirements for long-distance detection in radiation-irradiated environments such as the aerospace field. Summary of the invention

[0005] The main purpose of the present invention is to provide a leather glass composition, leather glass and its preparation method and application. The technical problem to be solved is how to prepare a leather glass that can simultaneously meet the requirements of wide spectral response, radiation resistance and low refractive index. The spectral transmittance is ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose; the refractive index is ≤1.50; the average linear thermal expansion coefficient in the range of 30-300℃ is 75×10 -7 / ℃~85×10 -7 / ℃; it can be kept at 910℃ for 5 hours without crystallization, and after melting, the glass has the advantages of no stones or bubbles inside, good anti-crystallization performance, good moisture resistance and stability, excellent chemical stability, etc. The thermal properties meet the requirements of the preparation process of optical fiber image transmission array. The leather glass is used in the environment of high radiation radiation and wide spectrum detection in the aerospace field, which can effectively improve the imaging clarity and service life of the glass, thereby being more suitable for practical use.

[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to a leather glass composition proposed by the present invention, it comprises, by mass percentage:

[0007]

[0008] In the above raw materials, the total content of impurities Fe, Cu and Mn is ≤3ppm, and the total content of impurities Nd, Pr, U, Er, Eu, Tb and Dy is ≤2ppm.

[0009] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to a method for preparing leather glass proposed by the present invention, it comprises the following steps:

[0010] S21 raw materials are measured to obtain a mixture; the mixture comprises, by mass percentage, 60-75% quartz sand, 1.5-15% boric acid, 1-5% aluminum oxide, 1-10% sodium carbonate, 1-8% potassium bifluoride, 1-8% calcium fluoride, 0-5% basic magnesium carbonate, 0-8% lithium carbonate, 0-5% zinc oxide, and 0-2% cerium oxide; in the above raw materials, the total content of impurities Fe, Cu and Mn is ≤3ppm, and the total content of impurities Nd, Pr, U, Er, Eu, Tb, and Dy is ≤2ppm;

[0011] S22: melting, clarifying and stirring the mixture; introducing oxygen into the glass liquid during the melting, clarifying and stirring steps; the utensils for preparing and melting the mixture are all made of non-metallic materials; the melting furnace for melting and clarifying is made of refractory materials, and the heavy metal content thereof is ≤5ppm;

[0012] S23 glass liquid is discharged, cast into shape, and annealed to obtain leather glass.

[0013] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0014] Preferably, in the aforementioned preparation method, the container for melting the mixed material is a crucible made of quartz; and the surface of the crucible is provided with a silicon oxide coating.

[0015] Preferably, in the aforementioned preparation method, the refractory material is a corrosion-resistant and high-temperature-resistant material, and its temperature resistance is ≥1700°C.

[0016] Preferably, in the aforementioned preparation method, the melting furnace is dedicated to the preparation of the skin glass.

[0017] Preferably, in the aforementioned preparation method, the mixed material is melted by adding the mixed material into the container in 3-5 times, each time at an interval of 0.5-2 hours.

[0018] Preferably, in the aforementioned preparation method, the melting temperature of the mixture is 1350-1400°C; the clarification stirring temperature is 1460-1530°C, and the clarification stirring temperature time is 1-2h; the discharge temperature is 1300-1350°C; the annealing temperature is 550-600°C, and the annealing time is 2-4h.

[0019] Preferably, in the aforementioned preparation method, the flow rate of oxygen introduced into the glass liquid is 0.04-0.18 mol / L / min.

[0020] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the present invention, a leather glass is characterized in that, at a thickness of 100 mm, in the wavelength range of 330 to 2000 nm, the spectral transmittance is ≥ 75%; at a 6.4 kGy irradiation dose for 500 h, the transmittance attenuation rate at 350 nm is ≤ 3%; the refractive index is ≤ 1.50; the average linear thermal expansion coefficient in the range of 30 to 300 ° C is 75×10 -7 / ℃~85×10 -7 / ℃; kept at 910℃ for 5 hours without crystallization.

[0021] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: According to the present invention, a kind of leather glass mentioned above is used in a wide spectrum response radiation resistant optical fiber image transmission array.

[0022] By means of the above technical solution, the leather glass composition, leather glass and preparation method and application thereof proposed by the present invention have at least the following advantages:

[0023] The leather glass composition, leather glass and its preparation method and application proposed in the present invention achieve good technical effects by controlling the composition and content of the leather glass and the purity of the raw materials. The spectral transmittance is ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose; the refractive index is ≤1.50; the average linear thermal expansion coefficient in the range of 30-300℃ is 75×10 -7 / ℃~85×10 -7 / ℃; it can be kept at 910℃ for 5 hours without crystallization. After melting, it has the advantages of no stones or bubbles inside the glass, good anti-crystallization performance, good moisture resistance and stability, excellent chemical stability, etc. The thermal properties meet the requirements of the fiber optic image transmission array preparation process, and can simultaneously meet the requirements of wide spectral response, radiation resistance and low refractive index, and has high transmittance in the ultraviolet region. Specifically, the present invention strictly controls the impurity components and contents of raw materials, uses high-purity raw materials for batching, and strictly controls the contents of Fe, Cu, Mn, etc., so that the content of coloring elements in all raw materials is controlled below 3ppm; when rare earth oxides such as Ce are used, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, Dy, etc. is strictly prohibited, so that the total content is controlled below 2ppm; since harmful impurities in glass, such as transition metal ions and heavy metal ions, have low electron transition energy, their electron absorption energy transitions under high-energy radiation, resulting in the glass having obvious absorption of ultraviolet rays in the ultraviolet region; the present invention provides a guarantee for the ultraviolet transmittance of glass materials by strictly limiting its purity.

[0024] Furthermore, the present invention controls the glass melting and molding process. On the one hand, the materials of the ingredients and containers used in the melting process are controlled to be non-metallic materials. If plastic products are involved, colorless and transparent materials are used, thereby preventing the container material from melting into the glass during the direct contact between the glass raw materials and the container, or impurities in the glass raw materials from entering the glass and causing adverse effects on the glass; on the other hand, by controlling the material of the melting furnace of the heating container / apparatus to be refractory material, the heavy metal content therein is strictly controlled to be ≤5ppm, thereby preventing the refractory material from affecting the composition of the glass through the container opening; at the same time, oxygen is always introduced into the glass liquid during the melting, clarifying and stirring process to make the glass liquid present a strong oxidizing atmosphere, thereby being able to accurately control the valence distribution of the variable valence elements, thereby ensuring that the glass has a high transmittance under radiation resistance.

[0025] The technical solution of the present invention can be used to prepare a skin glass with excellent comprehensive performance by strictly limiting the type, content and purity of the raw materials of the glass composition, and by strictly controlling the glass melting and molding process, no new impurity components are introduced into the glass during the glass melting and molding process, thereby ensuring that the composition ratio of the skin glass finally formed is basically stable at the composition ratio when the raw materials are fed, thereby ensuring that it can achieve a better balance between various properties, can simultaneously meet the requirements of wide spectrum response, radiation resistance and low refractive index, and also has a higher ultraviolet transmittance, and has high imaging clarity in radiation environments such as space. , long service life; thereby ensuring that the skin glass obtained by the present invention can be used in the optical fiber image transmission array, the glass has a spectral transmittance of ≥75% at a thickness of 100mm; after irradiation for 500h at a irradiation dose of 6.4kGy, the transmittance attenuation rate at 350nm is ≤3%, which improves the service life and stability of the skin glass in a ray irradiation environment; the refractive index is ≤1.50, which ensures that the optical fiber image transmission array has better light collecting ability; the skin glass of the present invention has the advantages of no stones and bubbles inside the glass after melting, good anti-crystallization performance, good moisture resistance stability, excellent chemical stability, etc., and the thermal properties meet the requirements of the preparation process of the optical fiber image transmission array.

[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0027] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a leather glass composition, leather glass and its preparation method and its specific implementation, structure, characteristics and effects of the application proposed by the present invention in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0028] The present invention provides a leather glass composition, which comprises, by mass percentage, 60-75% of quartz sand, 1.5-15% of boric acid, 1-5% of aluminum oxide, 1-10% of sodium carbonate, 1-8% of potassium bifluoride, 1-8% of calcium fluoride, 0-5% of basic magnesium carbonate, 0-8% of lithium carbonate, 0-5% of zinc oxide, and 0-2% of cerium oxide; in the above raw materials, the total content of impurities Fe, Cu and Mn is ≤3ppm, and the total content of impurities Nd, Pr, U, Er, Eu, Tb and Dy is ≤2ppm.

[0029] The above-mentioned skin glass composition can obtain a skin glass after melting, clarifying, stirring, molding and annealing. Each component in the skin glass exists in the form of oxides, that is, the skin glass contains SiO2, B2O3, Al2O3, Na2O, K2O, CaO, MgO, Li2O, ZnO, and CeO2.

[0030] In the above-mentioned leather glass, SiO2 is introduced in the form of quartz sand, which is the main body of the glass skeleton and the main component in the glass skeleton. In the leather glass, the weight percentage of quartz sand is 60-75%. When the content of quartz sand raw material is lower than 60%, it is difficult to obtain low refractive index glass, and the chemical resistance stability of the glass will also be reduced; when the content of quartz sand raw material is higher than 75%, the high temperature viscosity of the glass will increase, resulting in too high a melting temperature of the glass, and the thermal expansion coefficient of the glass will also be reduced.

[0031] B2O3 is introduced in the form of boric acid, which is an oxide for glass formation and also a component of the glass skeleton. It is also a solvent that reduces the viscosity of glass melting. Boron oxide triangle [BO3] and boron oxide tetrahedron [BO4] are structural components. Boron may exist in the form of triangle [BO3] or boron oxide tetrahedron [BO4] under different conditions. Under high temperature melting conditions, it is generally difficult to form boron oxide tetrahedron, and it can only exist in the form of trihedron. However, at low temperature, under certain conditions, B 3+ It has a tendency to capture free oxygen to form tetrahedrons, making the structure compact and increasing the low-temperature viscosity of the glass. However, due to its characteristics of reducing the viscosity of the glass at high temperatures and increasing the viscosity of the glass at low temperatures, it is also the main component that reduces the refractive index of the glass, which determines that its content range is relatively small. The preferred weight percentage of the boric acid raw material in the leather glass is 1.5-15. When the content of the boric acid raw material is greater than 15%, the refractive index of the glass will be reduced, and the phase separation tendency of the glass will also be increased.

[0032] Al2O3 is introduced as aluminum oxide, which is an intermediate oxide of glass. It can improve the radiation resistance of glass and reduce the phase separation tendency of glass. 3+ Prioritizes the formation of free oxygen [AlO4], which enters the glass network. 3+ Occupy Si 4+ Due to Al 3+ and Si 4+There are different valence states, which require alkali metal ions to fill and balance the valence state. The broken structural chains in the glass are linked again, the structure of the glass tends to be compact, the number of non-bridging oxygen is reduced, and the radiation resistance of the glass is improved. Therefore, within a certain content range, it can become the main body of glass network formation like SiO2. The weight percentage of aluminum oxide is 1-5%. When the content of aluminum oxide is greater than 5%, the high-temperature viscosity of the glass will be significantly increased, and the melting temperature of the glass will be increased.

[0033] Na2O is introduced in the form of sodium carbonate, which is an alkali metal oxide and an external oxide of the glass structure network. Na2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide spectrum transmittance of the glass. The weight percentage of the sodium carbonate raw material is preferably 1-10%. When the raw material content of sodium carbonate is greater than 10%, the refractive index and thermal expansion coefficient of the glass will increase, and the crystallization tendency of the glass will increase.

[0034] K2O is introduced in the form of potassium bifluoride, which is an alkali metal oxide and an external oxide of the glass structure network. K2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide spectrum transmittance of the glass. - The introduction of F can fill the oxygen vacancies in the glass, repair the structural defects and improve the glass transmittance. - The 8-electron structure is stabilized by using its strong binding effect on the outer electrons to reduce the number of high-energy free electrons generated by irradiation, avoid the formation of color centers, and improve the radiation resistance of the glass. The weight percentage of the potassium bifluoride raw material is preferably 1-8%. When the content of the potassium bifluoride raw material is greater than 8%, the refractive index and thermal expansion coefficient of the glass will be increased, and the crystallization tendency of the glass will be increased.

[0035] CaO is introduced in the form of calcium fluoride to improve the radiation resistance and wide spectrum transmittance of the glass. - The introduction of F can fill the oxygen vacancies in the glass, repair the structural defects and improve the glass transmittance. - In order to stabilize the 8-electron structure, the strong binding effect on the outer electrons is utilized to reduce the number of high-energy free electrons generated by irradiation, avoid the formation of color centers, and improve the radiation resistance of the glass. The weight percentage of calcium fluoride raw materials is 1-8%. When the calcium fluoride content is greater than 8%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0036] MgO is introduced in the form of basic magnesium carbonate, which is an external oxide of the glass structure network and is used to adjust the crystallization temperature of the glass. The weight percentage of the basic magnesium carbonate raw material is 0-5%. If the content of the basic magnesium carbonate raw material is greater than 5%, the crystallization tendency of the glass will be increased.

[0037] Li2O is introduced in the form of lithium carbonate and is an external oxide in the glass structure network. Lithium oxide has a small ionic radius and high electronegativity, and is easy to enter the glass structure network and exert a greater attraction on the surrounding molecules, which helps to densify the glass structure, reduce internal defects and scattering centers, and thus improve the transmittance of the glass. The weight percentage of lithium carbonate raw materials is 0-8%. When the content of lithium carbonate raw materials is greater than 8%, the expansion coefficient of the glass will be increased.

[0038] ZnO is introduced as zinc oxide, with a high bandgap and excitation binding energy, and a high absorption coefficient under certain radiation exposure. A small amount of introduction can improve the radiation resistance of glass. The weight percentage of zinc oxide is 0-5%. When the zinc oxide content is greater than 5%, the chemical resistance and thermal expansion coefficient of the glass will be reduced, and the tendency of crystallization will be increased.

[0039] CeO2 is introduced with cerium oxide, which is a rare earth oxide. Cerium is a variable valence element and is in a high valence state under irradiation. 4+ It can first absorb high-energy electrons or free electrons caused by radiation, causing the valence state of the ions to change without causing the establishment of color centers, thereby playing a role in radiation resistance. After the cerium element changes its valence, the element absorbs ultraviolet and visible light in the new valence state, which will also cause the transmittance of the optical fiber imaging array to decrease. 4+ It has strong absorption in the visible light region and is converted into Ce 3+ When the absorption in the spectral region above 300nm is very small. The appropriate amount of Ce element introduced, through the oxygen-enriched melting process, accurately controls the valence state of the element, so that the amount of cerium introduced can be minimized under the premise that the radiation resistance meets the requirements, thereby resolving the contradiction between ultraviolet transparency (no valence element in the composition as much as possible) and radiation resistance (introducing cerium, the valence element, into the composition to absorb high-energy electrons generated after high-energy radiation to avoid the formation of color centers), achieving radiation resistance while ensuring that the glass has a high transmittance in the ultraviolet region. The weight percentage of cerium oxide is 0-2%. When the content of cerium oxide is greater than 2%, the crystallization tendency of the glass will increase and the transmittance of the glass will also be reduced.

[0040] In the above technical scheme, by controlling the composition and content of the leather glass composition, a leather glass with good technical effect is obtained after melting and forming. The spectral transmittance of the leather glass composition is ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a dose of 6.4kGy; the refractive index is ≤1.50; the average linear thermal expansion coefficient in the range of 30-300℃ is 75×10 -7 / ℃~85×10 -7 / ℃; it can be kept at 910℃ for 5 hours without crystallization. After melting, it has the advantages of no stones or bubbles inside the glass, good anti-crystallization performance, good moisture resistance and stability, excellent chemical stability, etc. The thermal properties meet the requirements of the fiber optic image transmission array preparation process, and can simultaneously meet the requirements of wide spectrum response, radiation resistance and high refractive index, and has high transmittance in the ultraviolet region. Specifically, the present invention strictly controls the impurity components and contents of raw materials, uses high-purity raw materials for batching, and strictly controls the contents of metals such as Fe, Cu, and Mn in the raw materials, so that the content of coloring elements in all raw materials is controlled below 3ppm; when rare earth oxides such as Ce are used in the formula, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, and Dy should be strictly prohibited, so that the total content is controlled below 2ppm; since harmful impurities in the glass, such as transition metal ions and heavy metal ions, have low electron transition energy, they may undergo transition due to electron absorption energy under high-energy radiation, resulting in the glass having obvious absorption of ultraviolet rays in the ultraviolet region; the present invention provides a guarantee for the ultraviolet transmittance of the glass material by strictly limiting its purity, thereby achieving the technical effect of its high transmittance.

[0041] The present invention also provides a method for preparing leather glass, which comprises the following steps:

[0042] First, the raw materials are measured to obtain a mixture. In terms of mass percentage, the mixture includes: 60-75% quartz sand, 1.5-15% boric acid, 1-5% aluminum oxide, 1-10% sodium carbonate, 1-8% potassium bifluoride, 1-8% calcium fluoride, 0-5% basic magnesium carbonate, 0-8% lithium carbonate, 0-5% zinc oxide, and 0-2% cerium oxide; in the above raw materials, the total content of impurities Fe, Cu and Mn is ≤3ppm, and the total content of impurities Nd, Pr, U, Er, Eu, Tb, and Dy is ≤2ppm. The present invention has prepared a glass composition with good technical effect through a comprehensive design of the types, contents and purity of the raw materials.

[0043] In this step, the purity control of the raw materials is very critical, because the harmful impurities that may exist in the raw materials, such as transition metal ions and heavy metal ions, have low electron transition energy. When irradiated with high-energy rays, the electrons absorb energy and undergo transition, and they have obvious absorption of ultraviolet rays in the ultraviolet region. Therefore, in order to avoid their influence on the transmittance of the glass material in the ultraviolet region, the present invention strictly controls the content of harmful impurities in the oxides or salts used to prepare the leather glass composition. When preparing the composition, all raw materials are high-purity raw materials, and the content of Fe, Cu, Mn, etc. in the raw materials is strictly controlled, so that the content of coloring elements in all raw materials is controlled below 3ppm; when using rare earth oxides such as Ce, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, Dy, etc. is strictly prohibited, and the total content is controlled below 2ppm; thereby ensuring that the glass prepared by this technical solution has excellent comprehensive performance.

[0044] Furthermore, this step requires very high purity of the raw materials, so the containers and tools used in the batching process also need to be strictly controlled. For example, the material of the batching container is strictly controlled to be non-metallic; if it is a plastic product, it is preferably colorless and transparent; the reason for this arrangement is that: since the container, such as a crucible, will be in direct contact with the glass, whether it is the crucible material or impurities in the crucible, if they are brought into the mixture, they may melt into the glass during the subsequent melting process, which will have an adverse effect on the quality and performance of the glass. For example, if a platinum crucible is used, platinum particles or ions may enter the glass, which will cause ultraviolet absorption to be detrimental to the light transmittance of the glass; according to the composition of the skin glass in the present invention, a quartz crucible is preferably used, and a high-purity silicon oxide coating is provided on the surface of the crucible, so as to reduce the influence of the crucible components on the glass components and reduce the introduction of impurities.

[0045] The second step is to melt the prepared mixture, clarify and stir it. The container for melting the mixture is also made of non-metallic materials; the reason is as mentioned above, the present invention preferably uses a quartz crucible as the melting container, and the surface of the crucible is provided with a high-purity silicon oxide coating.

[0046] In this step, the mixed material can be directly added to the container for melting; however, in order to improve the melting efficiency and the quality of the molten glass, the present invention preferably adds the mixed material to the melting container in batches during melting; in some specific embodiments of the present invention, the mixed material is preferably added to the container in 3-5 times, each time with an interval of 0.5-2 hours; adding the mixed material in batches in this way can more efficiently complete the melting of the glass composition.

[0047] The melting process of the glass composition can be specifically adjusted according to its composition ingredients. Under the composition formula conditions designed in the technical solution of the present invention, the preferred melting temperature is 1350-1400° C., so that the glass composition can be melted quickly.

[0048] After the glass composition is completely melted, the glass liquid can be clarified and stirred. In this step, the clarification stirring temperature is preferably 1460-1530°C, and the clarification stirring temperature time is 1-2 hours; during the clarification process of the glass liquid, it is preferably stirred throughout the process, and the stirrer is preferably a double-bladed paddle to improve the stirring effect; the material of the stirrer is preferably non-metallic material to avoid contact with the glass liquid and the introduction of harmful impurities.

[0049] In order to ensure that the obtained leather glass can have a high transmittance under irradiation conditions, the present invention strictly limits the introduction of oxygen into the glass melt during the glass melting, clarification and stirring stages, so that the glass melt can be in a strong oxidizing atmosphere. The amount of oxygen introduced will adjust the concentration of the oxidizing atmosphere of the glass melt, so that the variable valence elements can be melted in an oxygen-rich environment, so that the glass melt has a sufficient amount of high-valence variable valence elements to meet the radiation resistance of the glass, while not making the amount of high-valence variable elements too high, resulting in the absorption of light by high-valence variable elements and affecting the transmittance of the glass. In some specific embodiments of the present invention, the flow rate of oxygen introduced into the glass melt is preferably 0.04-0.18 mol / L / min, so that the valence state of the radiation-resistant variable valence element cerium can be accurately adjusted to ensure that the leather glass has a high transmittance under irradiation conditions.

[0050] The melting of glass is generally carried out in an open crucible. Since the decomposition of the raw materials in the glass composition may produce a large amount of volatilized gas, and some components in the glass composition are also volatile, these volatile components will corrode the materials of the melting furnace, and the corroded materials may also affect the glass itself through the crucible mouth. For this reason, the present invention preferably uses refractory materials for the melting and clarification melting furnace, and strictly controls the content of heavy metals such as lead, cadmium, and mercury ≤5ppm, thereby directly reducing the adverse effects of the melting furnace material on the quality of the glass liquid; further, by preferably using the refractory material that is resistant to corrosion and high temperature, preferably with a temperature resistance of ≥1700°C, it can avoid or reduce the corrosion of the volatile components of the glass on the melting furnace, thereby indirectly reducing the adverse effects of the melting furnace material on the quality of the glass liquid.

[0051] Furthermore, in order to avoid cross-contamination of glass due to erosion of the refractory materials of the melting furnace, the present invention preferably uses a melting furnace that heats the container specifically for melting the skin glass, thereby avoiding or reducing cross-contamination caused by the melting furnace materials; further, even if the melting furnace is dedicated, the present invention may further preferably replace it regularly according to usage and erosion conditions, so that it can prevent harmful impurities such as Fe and Ti in the refractory materials from entering the glass, thereby avoiding or reducing the influence of the melting furnace on the composition of the molten glass.

[0052] Finally, the glass liquid is discharged, and the glass liquid is injected into the mold and cast into the required form of glass; annealing is performed to obtain the leather glass. The temperature and time of the discharge, molding and annealing of the glass liquid can be adjusted according to the actual composition of the glass composition. In some specific embodiments of the present invention, according to the composition of the glass composition, the discharge temperature is preferably 1300-1350°C, the annealing temperature is 550-600°C, and the annealing time is 2-4h.

[0053] The present invention also provides a leather glass, which has a spectral transmittance of ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm; a transmittance attenuation rate of ≤3% at 350nm after irradiation for 500h at a dose of 6.4kGy; a refractive index of ≤1.50; and an average linear thermal expansion coefficient of 75×10 -7 / ℃~85×10 -7 / ℃; kept at 910℃ for 5 hours without crystallization.

[0054] In some specific embodiments of the present invention, the skin glass is preferably prepared using the glass composition described above in the present invention; and the glass is preferably melted and clarified using the preparation method described above in the present invention. This description does not exclude other glass preparation methods that do not introduce harmful impurities.

[0055] The present invention also proposes an application of the aforementioned leather glass in a wide spectrum response radiation-resistant optical fiber imaging array.

[0056] The present invention also proposes an application of the aforementioned leather glass for long-distance detection in a radiation irradiation environment in the aerospace field.

[0057] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0058] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0059] Raw material requirements: quartz sand (4N, 160μm sieve material is less than 5%, 40μm sieve material is less than 5%), boric acid (analytical grade, 400μm sieve material is less than 10%, 63μm sieve material is less than 10%), zinc oxide (analytical grade), aluminum oxide (analytical grade, average particle size 50μm), sodium carbonate (analytical grade), potassium bifluoride (analytical grade), calcium fluoride (analytical grade), basic magnesium carbonate (chemically pure, average particle size 50μm), lithium carbonate (analytical grade), cerium oxide (4N). The total content of Fe, Cu, and Mn coloring elements in high-purity raw materials is strictly controlled to be less than 3ppm. When rare earth cerium oxide is used, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, and Dy is strictly prohibited, and the total content is controlled to be less than 2ppm.

[0060] Example 1

[0061] Melting of leather glass: Select raw materials according to the glass composition of Example 1 in Table 1, weigh the raw materials according to the ingredient list, mix them evenly and put them into a quartz crucible with a high-purity silicon oxide coating on the surface. The containers and utensils used in the batching and material processing are all made of non-metallic materials, and the plastic products are colorless and transparent. The content of lead, cadmium and mercury in the refractory material of the furnace top is controlled below 5ppm, and it is resistant to corrosion and high temperature above 1700℃. The smelting electric furnace must be dedicated to avoid cross contamination caused by erosion of the refractory material. It should be replaced regularly according to the use and corrosion conditions to prevent harmful impurities such as Fe and Ti in the refractory material from entering the glass.

[0062] The mixture is added to the crucible 5 times at intervals of 0.5 hours for high temperature melting at 1360°C. After the raw material mixture is melted, it is clarified and stirred at a temperature of 1470°C for 2 hours. The stirrer adopts a double-blade paddle to improve the stirring effect. During this melting and clarification stage, the oxygen valve is opened to introduce oxygen into the glass liquid at a flow rate of 0.044 mol / L / min to make the glass liquid present a strong oxidizing atmosphere. The melted and clarified glass liquid is discharged at 1300°C and cast into the required glass in a mold. After the glass is cooled and solidified, it is annealed at an annealing temperature of 550°C and a heat preservation time of 4 hours to obtain the leather glass of the present invention.

[0063] After testing, the leather glass prepared in this embodiment has a spectral transmittance of 75.8% in the wavelength range of 330-2000nm at a thickness of 100mm; a transmittance attenuation rate of 2.3% at 350nm after irradiation for 500h at a dose of 6.4kGy; a refractive index of 1.4985; and an average linear thermal expansion coefficient of 82×10 -7 / ℃; kept at 910℃ for 5 hours without crystallization.

[0064] Embodiment 2 to Embodiment 5

[0065] The process is the same as in Example 1. The formula of the leather glass composition, the purity of the raw materials and the process parameters are shown in Table 1. The test results are also shown in Table 1.

[0066] Table 1 Chemical composition, process parameters and properties of the leather glass of Examples 1 to 5

[0067]

[0068]

[0069] Note: a represents the total content of Fe, Cu, Mn and other coloring elements in high-purity reagent quartz sand and cerium oxide, in ppm; b represents the total content of Nd, Pr, U, Er, Eu, Tb, Dy impurities in cerium oxide, in ppm; c represents the spectral transmittance of 330nm~2000nm, in %; d represents the transmittance attenuation rate (irradiated for 500h at 6.4kGy irradiation dose, at 350nm), in %; e represents the refractive index; f represents the average linear thermal expansion coefficient in the range of 30~300℃, in ×10 -7 / ℃.

[0070] It can be seen from the test data shown in Table 1 that the leather glass prepared in the embodiment of the present invention has excellent comprehensive performance, which simultaneously meets the requirements of wide spectral response, radiation resistance and low refractive index, and has high transmittance in the ultraviolet region.

[0071] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0072] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A leather glass composition, characterized in that: In terms of mass percentage, it includes: In the above raw materials, the total content of impurities Fe, Cu and Mn is ≤3ppm, and the total content of impurities Nd, Pr, U, Er, Eu, Tb and Dy is ≤2ppm.

2. A method for preparing leather glass, characterized in that: It includes the following steps: S21 raw materials are measured to obtain a mixture; the mixture comprises, by mass percentage, 60-75% quartz sand, 1.5-15% boric acid, 1-5% aluminum oxide, 1-10% sodium carbonate, 1-8% potassium bifluoride, 1-8% calcium fluoride, 0-5% basic magnesium carbonate, 0-8% lithium carbonate, 0-5% zinc oxide, and 0-2% cerium oxide; in the above raw materials, the total content of impurities Fe, Cu and Mn is ≤3ppm, and the total content of impurities Nd, Pr, U, Er, Eu, Tb, and Dy is ≤2ppm; S22: melting, clarifying and stirring the mixture; introducing oxygen into the glass liquid during the melting, clarifying and stirring steps; the utensils for preparing and melting the mixture are all made of non-metallic materials; the melting furnace for melting and clarifying is made of refractory materials, and the heavy metal content thereof is ≤5ppm; S23 glass liquid is discharged, cast into shape, and annealed to obtain leather glass.

3. The preparation method according to claim 2, characterized in that: The container for melting the mixed material is a crucible made of quartz material; the surface of the crucible is provided with a silicon oxide coating.

4. The preparation method according to claim 3, characterized in that: The refractory material is a corrosion-resistant and high-temperature-resistant material, and its temperature resistance is ≥1700°C.

5. The preparation method according to claim 3, characterized in that: The melting furnace is specially used for preparing the leather glass.

6. The preparation method according to any one of claims 2 to 5, characterized in that: The mixed material is melted by adding the mixed material into the container in 3-5 times, each time at an interval of 0.5-2 hours.

7. The preparation method according to any one of claims 2 to 5, characterized in that: The melting temperature of the mixed material is 1350-1400° C.; the clarifying and stirring temperature is 1460-1530° C., and the clarifying and stirring temperature time is 1-2 hours; the discharging temperature is 1300-1350° C.; the annealing temperature is 550-600° C., and the annealing time is 2-4 hours.

8. The preparation method according to any one of claims 2 to 5, characterized in that: The flow rate of oxygen introduced into the glass liquid is 0.04-0.18 mol / L / min.

9. A leather glass, characterized in that: At a thickness of 100 mm, the spectral transmittance is ≥75% in the wavelength range of 330-2000 nm; the transmittance attenuation rate at 350 nm is ≤3% after irradiation for 500 h at a dose of 6.4 kGy; the refractive index is ≤1.50; the average linear thermal expansion coefficient in the range of 30-300 ° C is 75×10 -7 / ℃~85×10 -7 / ℃; kept at 910℃ for 5 hours without crystallization.

10. Use of the leather glass according to claim 9 in a wide spectral response radiation-resistant optical fiber imaging array.

Citation Information

Patent Citations

  • Anti-ultraviolet absorption space irradiation-resistant glass and manufacturing process thereof

    CN111875250A

  • Low-refractive-index glass for medium-expansion optical fiber image transmitting element and preparation method of low-refractive-index glass

    CN117602828A

  • Method for manufacturing float plate glass having excellent light transmittance

    KR1020140005111A

  • High-refractive-index radiation-resistant glass material, preparation method therefor, and use thereof

    WO2024178753A1